PEMBELAJARAN PENJUMLAHAN BILANGAN MENGGUNAKAN MEDIA POHON PINTAR : DESAIN PEMBELAJARAN DENGAN PENDEKATAN PMRI - Irma Irma; Hasan Basri; Andi Harpeni Dewantara (Didaktika : Jurnal Kependidikan, 2022)
This study aims at investigating how the usage of ‘smart tree’ manipulative media could support the first graders’ understanding of the addition concept. The research method is design research which consists of three stages, namely preliminary design, teaching experiment and retrospective analysis. The research subjects involved fifth grade students at an Islamic elementary school in Watampone in which 6 students were in the pilot experiment and 23 students involved in the teaching experiment. Data were collected through tests, interviews, documentation and field notes. The results shows that the implementation of Realistic Mathematics Education (RME) approach using ‘smart tree’ manipulative media could create a more enjoyable and meaningful addition learning for the first graders. The learning trajectory consists of two learning activities; organizing objects using familiar number/groups as well as doing addition activity using card game and smart tree manipulative media proved to be able to support students' understanding of the concept of addition from the informal level to the formal level.Keywords: addition; PMRI; smart tree; manipulative media